Research on the Evolution and Innovation of Guangdong Province’s Business Environment from a Digital Perspective - Feng, Jiajun; Liu, Zhengnan; Li, Tong (International Journal of Global Economics and Management, 2024)
This study, conducted against the backdrop of current digital development, systematically analyzes and discusses the status quo, problems, and countermeasures of the business environment in Guangdong Province. It reviews and critiques both domestic and international research on the definition of the business environment, the relationship between digitalization and the business environment, and the factors influencing the digitalization of the business environment. A comprehensive analysis of the internationalized business environment of Guangdong Province is presented, showcasing its advantages and characteristics in terms of digital infrastructure, digital technology innovation, and data element circulation, while also pointing out existing deficiencies and challenges. These serve as a reference for further optimization of the business environment. The article concludes by exploring and suggesting innovative pathways for Guangdong Province’s internationalized business environment, proposing a series of specific measures and plans to enhance digital innovation leadership capabilities and create a digitally empowered business environment. The aim is to promote the digital transformation and upgrading of Guangdong Province’s business environment, thereby improving its level of digital development and international competitiveness.